Exploring the capacity of minimalist protein interfaces: interface energetics and affinity maturation to picomolar K(D) of a single-domain antibody with a flat paratope - Koide, Akiko (2007)
A major architectural class in engineered binding proteins (“antibody mimics”) involves the presentation of recognition loops off a single-domain scaffold. This class of binding proteins, both natural and synthetic, has a strong tendency to bind a preformed cleft using a convex binding interface (paratope). To explore their capacity to produce high-affinity interfaces with diverse shape and topography, we examined the interface energetics and explored the affinity limit achievable with a flat paratope. We chose a minimalist paratope limited to two loops found in a natural camelid heavy-chain antibody (V(H)H) that binds to ribonuclease A. Ala scanning of the V(H)H revealed only three “hot-spot” side chains and additional four residues important for supporting backbone-mediated interactions. The small number of critical residues suggested that this is not an optimized paratope. Using selection from synthetic combinatorial libraries, we enhanced its affinity by >100 fold, resulting in variants with K(d) as low as 180 pM with no detectable loss of binding specificity. High-resolution crystal structures revealed that the mutations induced only subtle structural changes but extended the network of interactions. This resulted in an expanded hot-spot region including four additional residues located at the periphery of the paratope with a concomitant loss of the so-called “O-ring” arrangement of energetically inert residues. These results suggest that this class of simple, single-domain scaffolds is capable of generating high-performance binding interfaces with diverse shape. More generally they suggest that highly functional interfaces can be designed without closely mimicking natural interfaces.